Desulfurized gypsum-based loess foam goaf grouting filling material and preparation method thereof
Patent Information
- Application Number
- CN202510721481.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2026-10-13
AI Technical Summary
[0007]有鉴于此,本发明的目的在于提出脱硫石膏基黄土发泡采空区注浆充填材料及其制备方法,以解决现有技术中脱硫石膏基填充材料耐水性差、抗压强度低的问题
本发明提供了脱硫石膏基黄土发泡采空区注浆充填材料及其制备方法,本发明以脱硫石膏、黄土、水泥、粉煤灰和脱硫石膏组合物为主要成分,搭配防水剂、发泡剂等其他助剂,制备得到了一种耐水性强、抗压强度高的注浆充填材料;其中,由脱硫石膏、黄土、粉煤灰、水泥和防水剂B经混合、养护制备得到脱硫石膏组合物能有效加快充填材料中脱硫石膏早期的水化速度和抗压强度,且以甲基硅酸钠为壳、聚苯乙烯为核的、具有疏水性的改性甲基硅酸钠复合微胶囊,与甲基硅酸钠复配发挥协同作用,更好地提高充填材料的耐水性和抗压强度,与现有技术相比,具有广泛的应用前景。
Smart Images

Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of goaf treatment technology, and in particular to a desulfurized gypsum-based loess foamed goaf grouting and filling material and its preparation method. Background Technology
[0002] After mining, such as gold and coal mines, large underground voids are left behind. Prolonged periods of inactivity in these voids can lead to the collapse of the roof strata, causing surface subsidence and severely impacting farmland, buildings, and even the daily lives of residents. This poses a serious threat to the safety of surrounding buildings and people. Therefore, effective backfilling of these voids is crucial. Currently, commonly used backfilling materials such as cement-based materials are expensive, and the large-scale use of cement consumes significant resources and generates high carbon emissions. Traditional loess-based backfilling materials, on the other hand, suffer from low strength and poor fluidity, making them unsuitable for meeting the complex backfilling needs of mined-out areas.
[0003] Loess, as a widely available natural material, is abundant and easy to obtain. It is a fine-grained soil mainly composed of clay particles, and has porosity, looseness and good self-supporting properties. When filling mined-out areas, it has a certain degree of compaction and stability, and has been widely used in the treatment of mined-out areas.
[0004] Desulfurized gypsum is a byproduct of flue gas desulfurization in coal-fired power plants, its main component being calcium sulfate dihydrate (CaSO4•2H2O). To reduce sulfur dioxide emissions, coal-fired power plants typically employ a limestone-gypsum desulfurization process. In this process, flue gas from coal combustion passes through an absorption tower and comes into contact with limestone slurry. Sulfur dioxide is absorbed and reacts with the limestone to form calcium sulfite. Subsequently, the calcium sulfite is oxidized by oxidizing air to form calcium sulfate dihydrate, i.e., desulfurized gypsum. Desulfurized gypsum has many unique advantages over natural gypsum. First, it has higher purity and lower impurity content, with calcium sulfate dihydrate accounting for over 90% of its composition. Second, it has fine and uniform particles, typically around 10 μm in diameter, resulting in a larger specific surface area and higher reactivity. Third, its chemical composition is stable, less affected by changes in the external environment, and exhibits good physical and chemical stability. Furthermore, desulfurized gypsum is an industrial byproduct with wide availability, abundant resources, and relatively low price, possessing good economic and environmental benefits. The rational utilization of desulfurized gypsum in the preparation of backfill materials for mined-out areas can both realize the resource utilization of industrial solid waste and reduce backfilling costs.
[0005] However, desulfurized gypsum has poor water resistance and is often used in combination with cement and fly ash in goaf filling materials. In the prior art, patent document CN110510914A discloses a method for preparing a composite emulsion waterproofing agent to improve the water resistance of desulfurized gypsum. This raw material formulation includes 180-220 parts by weight of dimethyl silicone oil, 60-70 parts by weight of liquid paraffin, and 14-18 parts by weight of emulsifier. While this composite emulsion waterproofing agent can effectively improve the water resistance of desulfurized gypsum, it can affect the hydration process of the desulfurized gypsum. When added to desulfurized gypsum-based goaf filling materials, the overall compressive strength of the material needs further improvement.
[0006] Therefore, based on the relevant technologies mentioned above, there is an urgent need to develop desulfurized gypsum-based loess foamed grouting filling materials for goaf areas and their preparation methods. Summary of the Invention
[0007] In view of this, the purpose of this invention is to propose a desulfurized gypsum-based loess foamed goaf grouting filling material and its preparation method, so as to solve the problems of poor water resistance and low compressive strength of existing desulfurized gypsum-based filling materials.
[0008] To achieve the above objectives, this invention provides a desulfurized gypsum-based foamed loess grouting filling material for goaf areas and its preparation method.
[0009] The desulfurized gypsum-based loess foamed grouting filling material for goaf areas includes the following raw materials by weight: 32-48 parts desulfurized gypsum; 22-35 parts loess; 8-14 parts cement; 15-24 parts fly ash; 10-13 parts slag; 3-5 parts β-hemihydrate gypsum; 18-23 parts desulfurized gypsum composition; 1.6-2.3 parts waterproofing agent A; 0.9-1.4 parts early strength agent; 66-84 parts deionized water; 0.2-0.35 parts foaming agent; 0.1-0.3 parts foam stabilizer; The waterproofing agent A is obtained by mixing sodium methylsilicate and modified sodium methylsilicate composite microcapsules at a mass ratio of 17-21:5.5-8.3; The modified sodium methylsilicate composite microcapsules were prepared from sodium methylsilicate, dodecyl dimethylpropylamine sulfonic acid, and styrene. The desulfurized gypsum composition is prepared from desulfurized gypsum, loess, fly ash, cement and waterproofing agent B; The waterproofing agent B is a styrene-acrylate emulsion.
[0010] Preferably, the modified sodium methylsilicate composite microcapsules are prepared as follows: Step A1. Add deionized water to a three-necked flask, add dodecyl dimethyl propylamine sulfonic acid while stirring, mix well, then add styrene dropwise, continue stirring for 25-30 minutes, heat to T1, add 10% potassium persulfate aqueous solution to the system, heat the reaction at T1 temperature, cool to room temperature, and obtain mixture 1. Step A2. Add a 25% sodium methylsilicate aqueous solution to a beaker, and add sodium dihydrogen phosphate and disodium hydrogen phosphate to adjust the pH of the system to 6-7 to obtain mixture 2; Step A3. Add mixture 2 dropwise to mixture 1, stir evenly, heat to T2 for heating reaction, centrifuge, wash and dry to obtain modified sodium methylsilicate composite microcapsules.
[0011] Preferably, the ratio of deionized water, dodecyl dimethyl propylamine sulfonic acid, styrene and potassium persulfate aqueous solution in step A1 is 72-80 mL: 1.6-2 g: 13-15.7 mL: 4.4-5 mL; The temperature T1 is 68-73℃; The heating reaction takes 2-2.5 hours.
[0012] Preferably, the volume ratio of mixture 1 to mixture 2 in step A3 is 105-115:19-23; The temperature T2 is 45-55℃; The heating reaction takes 3.5-4 hours.
[0013] Preferably, the desulfurized gypsum composition is prepared as follows: Desulfurized gypsum, loess, fly ash, and cement are mixed, and then styrene-acrylate emulsion and deionized water are added. After mixing evenly, the mixture is left to stand for aging and curing to obtain a desulfurized gypsum composition. The ratio of the amount of desulfurized gypsum, loess, fly ash, cement, styrene-acrylate emulsion and deionized water is 5-8g:3-5g:9-13g:9-13g:0.15-0.25mL:2-3mL.
[0014] Preferably, the settling and aging time is 20-24 hours; The curing conditions are: steam curing at 60-65℃ for 15-20 hours.
[0015] Preferably, the desulfurized gypsum has a fineness ≤12.0%, a water requirement ≤95%, and a loss on ignition ≤5.0%. The cement is ordinary Portland cement; The fly ash has a particle size of <10μm and a specific surface area of 700-1000m². 2 / kg; The slag is a highly activated alkaline slag with a particle size of 5-12 mm.
[0016] Preferably, the loess is silty loess with a particle content of not less than 60% and a particle size of less than 0.15 mm; The foaming agent is sodium dodecyl sulfate.
[0017] Preferably, the foam stabilizer is polyacrylamide; The early strength agent is any one of calcium chloride, sodium sulfate, and calcium formate.
[0018] A method for preparing desulfurized gypsum-based loess foamed grouting filling material for goaf areas includes the following steps: Step S1. Add the foaming agent to one-fifth of the deionized water and stir for 15-20 minutes to obtain the foaming agent solution; Step S2. Dry the desulfurized gypsum at 125-140℃ to constant weight, pass it through a 0.15mm square hole sieve, and mix it evenly with cement, loess, fly ash, slag, desulfurized gypsum composition and β-hemihydrate gypsum. Add foam stabilizer, waterproofing agent A, early strength agent and four-fifths of deionized water, continue stirring for 20-30 minutes, add more, stir evenly to obtain mixture 3; Step S3. The foaming agent solution is foamed using a foaming machine, and the resulting foam is added to the mixture 3 and stirred for 3-5 minutes to obtain the desulfurized gypsum-based loess foamed goaf grouting and filling material.
[0019] The beneficial effects of this invention are: This invention provides a desulfurized gypsum-based loess foamed grouting filling material for goaf areas and its preparation method. The invention uses a composition of desulfurized gypsum, loess, cement, fly ash, and desulfurized gypsum as the main components, combined with waterproofing agents, foaming agents, and other additives, to prepare a grouting filling material with strong water resistance and high compressive strength. Specifically, the desulfurized gypsum composition prepared by mixing and curing desulfurized gypsum, loess, fly ash, cement, and waterproofing agent B can effectively accelerate the early hydration rate and compressive strength of the desulfurized gypsum in the filling material. Furthermore, the hydrophobic modified sodium methylsilicate composite microcapsules with sodium methylsilicate as the shell and polystyrene as the core work synergistically with sodium methylsilicate to further improve the water resistance and compressive strength of the filling material. Compared with existing technologies, this invention has broad application prospects. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0021] The sources and properties of some of the raw materials used in this invention are as follows: Sodium sulfate was purchased from Shanghai Chenqi Chemical Co., Ltd.; calcium chloride was purchased from Shanghai Chenqi Chemical Co., Ltd.; sodium methylsilicate was purchased from Jinan Hengjiu Chemical Co., Ltd.; dodecyl dimethyl propylamine sulfonic acid was purchased from Jinjinle (Hunan) Chemical Co., Ltd.; styrene was purchased from Nantong Chemical Light Industry Co., Ltd.; the cement was No. 42.5 ordinary silicate cement; and the styrene-acrylate emulsion was purchased from Guangdong Henghe Yongsheng Group Co., Ltd.
[0022] Example 1: A method for preparing desulfurized gypsum-based loess foamed grouting filling material for goaf areas, comprising the following steps: S1. Add 72 mL of deionized water to a three-necked flask, add 1.6 g of dodecyl dimethyl propyl aminosulfonic acid while stirring, mix well, then add 13 mL of styrene dropwise, continue stirring for 25 min, raise the temperature to 68 °C, add 4.4 mL of 10% potassium persulfate aqueous solution to the system, heat the reaction at 68 °C for 2 h, cool to room temperature, and obtain mixture 1; S2. Add a 25% sodium methylsilicate aqueous solution to a beaker, and add sodium dihydrogen phosphate and disodium hydrogen phosphate to adjust the pH of the system to 6, to obtain mixture 2; S3. Add 19 mL of mixture 2 dropwise to 105 mL of mixture 1, stir evenly, heat to 45 °C and react for 3.5 h, centrifuge, wash and dry to obtain modified sodium methylsilicate composite microcapsules; S4. Mix 5g desulfurized gypsum, 3g loess, 9g fly ash and 9g cement, then add 0.15mL styrene-acrylate emulsion and 2mL deionized water. After mixing evenly, let stand for 20h and steam at 60℃ for 15h to obtain the desulfurized gypsum composition. S5. Add 0.2g sodium dodecyl sulfate to one-fifth of deionized water and stir for 15 minutes to obtain a foaming agent solution; mix 17g sodium methylsilicate with 5.5g modified sodium methylsilicate composite microcapsules to obtain waterproofing agent A; S6. Dry 32g of desulfurized gypsum at 125℃ to constant weight, pass it through a 0.15mm square hole sieve, and mix it evenly with 8g of cement, 22g of loess, 15g of fly ash, 10g of slag, 18g of desulfurized gypsum composition and 3g of β-hemihydrate gypsum. Add 0.1g of polyacrylamide, 1.6g of waterproofing agent A, 0.9g of sodium sulfate and four-fifths of deionized water, continue stirring for 20min, add more, stir evenly to obtain mixture 3; S7. The foaming agent solution is foamed using a foaming machine, and the resulting foam is added to the mixture 3 and stirred for 3 minutes to obtain the desulfurized gypsum-based loess foamed goaf grouting and filling material.
[0023] Example 2: A method for preparing desulfurized gypsum-based loess foamed grouting filling material for goaf areas, comprising the following steps: S1. Add 74 mL of deionized water to a three-necked flask, add 1.7 g of dodecyl dimethyl propylamine sulfonic acid while stirring, mix well, then add 13.5 mL of styrene dropwise, continue stirring for 26 min, raise the temperature to 70 °C, add 4.6 mL of 10% potassium persulfate aqueous solution to the system, heat the reaction at 70 °C for 2 h, cool to room temperature, and obtain mixture 1; S2. Add a 25% sodium methylsilicate aqueous solution to a beaker, and add sodium dihydrogen phosphate and disodium hydrogen phosphate to adjust the pH of the system to 6, to obtain mixture 2; S3. Add 20 mL of mixture 2 dropwise to 107 mL of mixture 1, stir evenly, heat to 47 °C and react for 3.5 h, centrifuge, wash and dry to obtain modified sodium methylsilicate composite microcapsules; S4. Mix 6g desulfurized gypsum, 3.4g loess, 10g fly ash, and 10g cement, then add 0.17mL styrene-acrylate emulsion and 2.3mL deionized water. After mixing evenly, let stand for 21h and steam at 62℃ for 16h to obtain the desulfurized gypsum composition. S5. Add 0.24g sodium dodecyl sulfate to one-fifth of deionized water and stir for 16 minutes to obtain a foaming agent solution; mix 18g sodium methylsilicate with 6g modified sodium methylsilicate composite microcapsules to obtain waterproofing agent A; S6. Dry 36g of desulfurized gypsum at 130℃ to constant weight, pass it through a 0.15mm square hole sieve, and mix it evenly with 9g of cement, 25g of loess, 17g of fly ash, 11g of slag, 19g of desulfurized gypsum composition and 3.5g of β-hemihydrate gypsum. Add 0.17g of polyacrylamide, 1.8g of waterproofing agent A, 1g of sodium sulfate and four-fifths of deionized water, continue stirring for 22min, add more, stir evenly to obtain mixture 3; S7. The foaming agent solution is foamed using a foaming machine, and the resulting foam is added to the mixture 3 and stirred for 3 minutes to obtain the desulfurized gypsum-based loess foamed goaf grouting and filling material.
[0024] Example 3: A method for preparing desulfurized gypsum-based loess foamed grouting filling material for goaf areas, comprising the following steps: S1. Add 76 mL of deionized water to a three-necked flask, add 1.8 g of dodecyl dimethyl propylamine sulfonic acid while stirring, mix well, then add 14 mL of styrene dropwise, continue stirring for 28 min, heat to 70 °C, add 4.7 mL of 10% potassium persulfate aqueous solution to the system, heat at 70 °C for 2 h, cool to room temperature, and obtain mixture 1; S2. Add a 25% sodium methylsilicate aqueous solution to a beaker, and add sodium dihydrogen phosphate and disodium hydrogen phosphate to adjust the pH of the system to 7, to obtain mixture 2; S3. Add 21 mL of mixture 2 dropwise to 110 mL of mixture 1, stir evenly, heat to 50 °C and react for 3.5 h, centrifuge, wash and dry to obtain modified sodium methylsilicate composite microcapsules; S4. Mix 7g desulfurized gypsum, 4g loess, 11g fly ash and 11g cement, then add 0.2mL styrene-acrylate emulsion and 2.5mL deionized water. After mixing evenly, let stand for 22h and steam at 63℃ for 17h to obtain the desulfurized gypsum composition. S5. Add 0.28g sodium dodecyl sulfate to one-fifth of deionized water and stir for 17 minutes to obtain a foaming agent solution; mix 19g sodium methylsilicate with 6.5g modified sodium methylsilicate composite microcapsules to obtain waterproofing agent A; S6. Dry 42g of desulfurized gypsum at 135℃ to constant weight, pass it through a 0.15mm square hole sieve, and mix it evenly with 10g of cement, 29g of loess, 19g of fly ash, 12g of slag, 20g of desulfurized gypsum composition and 4g of β-hemihydrate gypsum. Add 0.2g of polyacrylamide, 2g of waterproofing agent A, 1.1g of sodium sulfate and four-fifths of deionized water, continue stirring for 25min, add more, stir evenly to obtain mixture 3; S7. The foaming agent solution is foamed using a foaming machine, and the resulting foam is added to the mixture 3 and stirred for 4 minutes to obtain the desulfurized gypsum-based loess foamed goaf grouting and filling material.
[0025] Example 4: A method for preparing desulfurized gypsum-based loess foamed grouting filling material for goaf areas, comprising the following steps: S1. Add 78 mL of deionized water to a three-necked flask, add 1.9 g of dodecyl dimethyl propylamine sulfonic acid while stirring, mix well, then add 14.3 mL of styrene dropwise, continue stirring for 30 min, raise the temperature to 73 °C, add 4.8 mL of 10% potassium persulfate aqueous solution to the system, heat the reaction at 73 °C for 2.5 h, cool to room temperature, and obtain mixture 1; S2. Add a 25% sodium methylsilicate aqueous solution to a beaker, and add sodium dihydrogen phosphate and disodium hydrogen phosphate to adjust the pH of the system to 7, to obtain mixture 2; S3. Add 22 mL of mixture 2 dropwise to 112 mL of mixture 1, stir evenly, heat to 53℃ and react for 4 h, centrifuge, wash and dry to obtain modified sodium methylsilicate composite microcapsules; S4. Mix 7g desulfurized gypsum, 4.5g loess, 12g fly ash, and 12g cement, then add 0.23mL styrene-acrylate emulsion and 2.8mL deionized water. After mixing evenly, let stand for 23 hours and steam at 63℃ for 19 hours to obtain the desulfurized gypsum composition. S5. Add 0.32g sodium dodecyl sulfate to one-fifth of deionized water and stir for 20 minutes to obtain a foaming agent solution; mix 20g sodium methylsilicate with 7.8g modified sodium methylsilicate composite microcapsules to obtain waterproofing agent A; S6. Dry 45g of desulfurized gypsum at 135℃ to constant weight, pass it through a 0.15mm square hole sieve, and mix it evenly with 13g of cement, 32g of loess, 21g of fly ash, 12g of slag, 22g of desulfurized gypsum composition and 4.5g of β-hemihydrate gypsum. Add 0.25g of polyacrylamide, 2.2g of waterproofing agent A, 1.3g of calcium chloride and four-fifths of deionized water, continue stirring for 27min, add more, stir evenly to obtain mixture 3; S7. The foaming agent solution is foamed using a foaming machine, and the resulting foam is added to the mixture 3 and stirred for 5 minutes to obtain the desulfurized gypsum-based loess foamed goaf grouting and filling material.
[0026] Example 5: A method for preparing desulfurized gypsum-based loess foamed grouting filling material for goaf areas, comprising the following steps: S1. Add 80 mL of deionized water to a three-necked flask, add 2 g of dodecyl dimethyl propylamine sulfonic acid while stirring, mix well, then add 15.7 mL of styrene dropwise, continue stirring for 30 min, raise the temperature to 73 °C, add 5 mL of 10% potassium persulfate aqueous solution to the system, heat the reaction at 73 °C for 2.5 h, cool to room temperature, and obtain mixture 1; S2. Add a 25% sodium methylsilicate aqueous solution to a beaker, and add sodium dihydrogen phosphate and disodium hydrogen phosphate to adjust the pH of the system to 7, to obtain mixture 2; S3. Add 23 mL of mixture 2 dropwise to 115 mL of mixture 1, stir evenly, heat to 55 °C and react for 4 h, centrifuge, wash and dry to obtain modified sodium methylsilicate composite microcapsules; S4. Mix 8g of desulfurized gypsum, 5g of loess, 13g of fly ash and 13g of cement, then add 0.25mL of styrene-acrylate emulsion and 3mL of deionized water. After mixing evenly, let stand for 24 hours and steam at 65℃ for 20 hours to obtain the desulfurized gypsum composition. S5. Add 0.35g sodium dodecyl sulfate to one-fifth of deionized water and stir for 20 minutes to obtain a foaming agent solution; mix 21g sodium methylsilicate with 8.3g modified sodium methylsilicate composite microcapsules to obtain waterproofing agent A; S6. Dry 48g of desulfurized gypsum at 140℃ to constant weight, pass it through a 0.15mm square hole sieve, and mix it evenly with 14g of cement, 35g of loess, 24g of fly ash, 13g of slag, 23g of desulfurized gypsum composition and 5g of β-hemihydrate gypsum. Add 0.3g of polyacrylamide, 2.3g of waterproofing agent A, 1.4g of calcium formate and four-fifths of deionized water, continue stirring for 30min, add more, stir evenly to obtain mixture 3; S7. The foaming agent solution is foamed using a foaming machine, and the resulting foam is added to the mixture 3 and stirred for 5 minutes to obtain the desulfurized gypsum-based loess foamed goaf grouting and filling material.
[0027] Comparative Example 1: Compared with Example 1, this comparative example did not add the desulfurized gypsum composition during the preparation of the filling material. All other steps and parameters were the same, and will not be repeated here. The final filling material was obtained.
[0028] Comparative Example 2: Compared with Example 1, this comparative example did not add water-resistant agent A during the preparation of the filling material. All other steps and parameters were the same, and will not be repeated here. The final filling material was obtained.
[0029] Comparative Example 3: Compared with Example 1, this comparative example did not add water-resistant agent B during the preparation of the filling material. All other steps and parameters were the same, and will not be repeated here. The final filling material was obtained.
[0030] Comparative Example 4: Compared with Example 1, this comparative example did not add β-hemihydrate gypsum during the preparation of the filling material. All other steps and parameters were the same, and will not be repeated here. The final filling material was obtained.
[0031] Comparative Example 5: This comparative example differs from Example 1 only in that "water-resistant agent B" is replaced with "sodium methylsilicate". All other steps and parameters are the same, and will not be repeated here. The final filling material is obtained.
[0032] Comparative Example 6: Compared with Example 1, this comparative example only replaces "water-resistant agent B" with "modified sodium methylsilicate composite microcapsules". All other steps and parameters are the same, and will not be repeated in this comparative example. The final filling material is obtained.
[0033] Performance testing: Compressive strength: A 70.7mm×70.7mm×70.7mm triple mold was used for molding. After compaction on a vibration table, the filling materials prepared in Examples 1-5 and Comparative Examples 1-6 were placed in a standard curing room for curing (temperature 20±2℃, relative humidity above 90%). The compressive strength at 3d, 7d, and 28d was tested using a pressure testing machine. Porosity: Specimens measuring 150mm × 150mm × 150mm were cured in a standard curing room (temperature 20±2℃, relative humidity above 90%) for 7 days, then placed in an oven at 105±5℃ until constant weight. Afterward, they were removed and cooled to room temperature in a desiccator, and their volume V was measured. The specimens were then placed in water, and their weight m1 was measured when no more bubbles appeared. The specimens were then removed and dried in a 60℃ oven for 24 hours, and their weight m2 was measured again. The porosity was obtained and calculated as follows: υ=(1- )×100% Where υ is the porosity (%), m1 is the weight of the specimen in water (g), m2 is the weight of the specimen after drying for 24 hours (g), and ρ is the density of water (g / cm³). 3 V is the volume of the specimen (cm³). 3 ); Water resistance: A 70.7mm×70.7mm×70.7mm triple mold was used for molding. After compaction on a vibration table, the filling materials prepared in Examples 1-5 and Comparative Examples 1-6 were placed in a standard curing room for 28 days (temperature 20±2℃, relative humidity above 90%). After the specimens reached 28 days of age, they were removed from the standard curing environment and immersed in clean water at (20±3)℃ for 30 days. During the immersion process, the specimens should be completely submerged in water to simulate a long-term underwater environment. After immersion, the specimens were removed from the water and subjected to compressive strength testing to obtain the compressive strength of the specimens in water. Similarly, after the specimens reached 28 days of age, they were continued to be cured in the standard curing environment for 30 days, and then removed and subjected to compressive strength testing to obtain the compressive strength of the specimens in a terrestrial environment. The water-to-terrestrial strength ratio was calculated.
[0034] Water-to-land intensity ratio (R) = ×100% Table 1 Data Analysis: As shown in Table 1, the grouting filling material prepared by this invention has better water resistance, compressive strength, and less porosity. This may be because desulfurized gypsum has a slow crystallization process, resulting in slow early hydration and low compressive strength in the filling material. In contrast, the desulfurized gypsum composition prepared by mixing and curing desulfurized gypsum, loess, fly ash, cement, and waterproofing agent B has a dense microstructure and fewer pores. The styrene-acrylate emulsion of waterproofing agent B forms a hydrophobic film on its surface. Adding this to the filling material reduces the water absorption rate of the desulfurized gypsum, improves the structural density and overall mechanical properties of the material. Furthermore, the addition of the desulfurized gypsum composition can accelerate the early hydration rate of the desulfurized gypsum in the filling material, given the slow crystallization process and low early hydration and compressive strength of the desulfurized gypsum itself. Meanwhile, β-hemihydrate stone... The paste has uniform particles and a large specific surface area, providing more reaction sites. Compared with desulfurized gypsum, it has the advantages of shorter setting time and faster hydration rate. In the modified sodium methylsilicate composite microcapsules, the siloxane groups in sodium methylsilicate undergo hydrolysis and condensation reactions to form microcapsules with sodium methylsilicate as the shell and polystyrene as the core. On the one hand, the addition of these hydrophobic microcapsules to the filler material enhances the waterproofness of the system to a certain extent and reduces the porosity of the material, thereby improving the compressive strength and mechanical properties of the material. On the other hand, when combined with sodium methylsilicate, the two work synergistically. The resulting waterproofing agent A can form a hydrophobic film on the surface of desulfurized gypsum, improving the water resistance of the filler material, and also improve the poor mechanical properties when sodium methylsilicate is added alone as a waterproofing agent in the filler material.
[0035] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
[0036] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A desulfurized gypsum-based foamed loess grouting and filling material for goaf areas, characterized in that, Includes the following quantities of raw materials: 32-48 parts desulfurized gypsum; 22-35 parts loess; 8-14 parts cement; 15-24 parts fly ash; 10-13 parts slag; 3-5 parts β-hemihydrate gypsum; 18-23 parts desulfurized gypsum composition; 1.6-2.3 parts waterproofing agent A; 0.9-1.4 parts early strength agent; 66-84 parts deionized water; 0.2-0.35 parts foaming agent; 0.1-0.3 parts foam stabilizer; The waterproofing agent A is obtained by mixing sodium methylsilicate and modified sodium methylsilicate composite microcapsules at a mass ratio of 17-21:5.5-8.3; The modified sodium methylsilicate composite microcapsules were prepared from sodium methylsilicate, dodecyl dimethylpropylamine sulfonic acid, and styrene. The desulfurized gypsum composition is prepared from desulfurized gypsum, loess, fly ash, cement and waterproofing agent B; The waterproofing agent B is a styrene-acrylate emulsion.
2. The desulfurized gypsum-based loess foamed goaf grouting and filling material according to claim 1, characterized in that, The preparation method of the modified sodium methylsilicate composite microcapsules is as follows: Step A1. Add deionized water to a three-necked flask, add dodecyl dimethyl propylamine sulfonic acid while stirring, mix well, then add styrene dropwise, continue stirring for 25-30 minutes, heat to T1, add 10% potassium persulfate aqueous solution to the system, heat the reaction at T1 temperature, cool to room temperature, and obtain mixture 1. Step A2. Add a 25% sodium methylsilicate aqueous solution to a beaker, and add sodium dihydrogen phosphate and disodium hydrogen phosphate to adjust the pH of the system to 6-7 to obtain mixture 2; Step A3. Add mixture 2 dropwise to mixture 1, stir evenly, heat to T2 for heating reaction, centrifuge, wash and dry to obtain modified sodium methylsilicate composite microcapsules.
3. The desulfurized gypsum-based loess foamed goaf grouting and filling material according to claim 2, characterized in that, The ratio of deionized water, dodecyl dimethyl propylamine sulfonic acid, styrene, and potassium persulfate aqueous solution used in step A1 is 72-80 mL: 1.6-2 g: 13-15.7 mL: 4.4-5 mL; The temperature T1 is 68-73℃; The heating reaction takes 2-2.5 hours.
4. The desulfurized gypsum-based loess foamed goaf grouting and filling material according to claim 2, characterized in that, The volume ratio of mixture 1 to mixture 2 in step A3 is 105-115:19-23; The temperature T2 is 45-55℃; The heating reaction takes 3.5-4 hours.
5. The desulfurized gypsum-based loess foamed goaf grouting and filling material according to claim 1, characterized in that, The preparation method of the desulfurized gypsum composition is as follows: Desulfurized gypsum, loess, fly ash, and cement are mixed, and then styrene-acrylate emulsion and deionized water are added. After mixing evenly, the mixture is left to stand for aging and curing to obtain a desulfurized gypsum composition. The ratio of the amount of desulfurized gypsum, loess, fly ash, cement, styrene-acrylate emulsion and deionized water is 5-8g:3-5g:9-13g:9-13g:0.15-0.25mL:2-3mL.
6. The desulfurized gypsum-based loess foamed goaf grouting and filling material according to claim 5, characterized in that, The settling and aging time is 20-24 hours; The curing conditions are: steam curing at 60-65℃ for 15-20 hours.
7. The desulfurized gypsum-based loess foamed goaf grouting and filling material according to claim 1, characterized in that, The desulfurized gypsum has a fineness ≤12.0%, a water requirement ≤95%, and a loss on ignition ≤5.0%. The cement is ordinary Portland cement; The fly ash has a particle size of <10μm and a specific surface area of 700-1000m². 2 / kg; The slag is a highly activated alkaline slag with a particle size of 5-12 mm.
8. The desulfurized gypsum-based loess foamed goaf grouting and filling material according to claim 1, characterized in that, The loess is silty loess with a particle content of not less than 60% and a particle size of less than 0.15 mm; The foaming agent is sodium dodecyl sulfate.
9. The desulfurized gypsum-based loess foamed goaf grouting and filling material according to claim 1, characterized in that, The foam stabilizer is polyacrylamide; The early strength agent is any one of calcium chloride, sodium sulfate, and calcium formate.
10. The preparation method of the desulfurized gypsum-based loess foamed goaf grouting and filling material according to any one of claims 1-9, characterized in that, Includes the following steps: Step S1. Add the foaming agent to one-fifth of the deionized water and stir for 15-20 minutes to obtain the foaming agent solution; Step S2. Dry the desulfurized gypsum at 125-140℃ to constant weight, pass it through a 0.15mm square hole sieve, and mix it evenly with cement, loess, fly ash, slag, desulfurized gypsum composition and β-hemihydrate gypsum. Add foam stabilizer, waterproofing agent A, early strength agent and four-fifths of deionized water, continue stirring for 20-30 minutes, add more, stir evenly to obtain mixture 3; Step S3. The foaming agent solution is foamed using a foaming machine, and the resulting foam is added to the mixture 3 and stirred for 3-5 minutes to obtain the desulfurized gypsum-based loess foamed goaf grouting and filling material.
Citation Information
Patent Citations
Composite emulsion waterproofing agent for improving water resistance of desulfurized gypsum and preparation method thereof
CN110510914A